Properties of Components in Contact Systems - Zola, S.; Gazeas, K.; Kreiner, J. M.; Zakrzewski, B. (Astrophysics and Space Science, 2006)
A new sample of contact systems, consisting of more than 100 stars, was created for binaries for which the physical parameters have been determined using both photometric light curves and radial velocity measurements of both components. Properties of components are discussed including their evolutionary status.
Keywords: binaries: close; binaries: contact; binaries: eclipsing